2014
DOI: 10.1371/journal.pone.0094452
|View full text |Cite
|
Sign up to set email alerts
|

How the Impact of Median Neuropathy on Sensorimotor Control Capability of Hands for Diabetes: An Achievable Assessment from Functional Perspectives

Abstract: To comprehend the sensorimotor control ability in diabetic hands, this study investigated the sensation, motor function and precision pinch performances derived from a pinch-holding-up activity (PHUA) test of the hands of diabetic patients and healthy subjects. The precision, sensitivity and specificity of the PHUA test in the measurements of diabetic patients were also analyzed. We hypothesized that the diabetic hands would have impacts on the sensorimotor functions of the hand performances under functionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…In practice, precision pinch performance relies on the complex integration of impulses transmitted from sensory receptors, as well as control of muscle effectors. Therefore, it is likely to have better sensitivity and accuracy in determining asymptomatic neuropathy in hands of diabetic patients than pure sensory or strength tests . The use of rather crude methods to prevent objects slipping from their hands, as was found for the patients with longer diabetes duration in the current study, is associated with the development of microangiopathic complications .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In practice, precision pinch performance relies on the complex integration of impulses transmitted from sensory receptors, as well as control of muscle effectors. Therefore, it is likely to have better sensitivity and accuracy in determining asymptomatic neuropathy in hands of diabetic patients than pure sensory or strength tests . The use of rather crude methods to prevent objects slipping from their hands, as was found for the patients with longer diabetes duration in the current study, is associated with the development of microangiopathic complications .…”
Section: Discussionmentioning
confidence: 71%
“…However, the results of the 2PD tests in the current study did not differ significantly between the groups categorized by glycaemic control. There was also no evidence in previous studies regarding the impact of glycaemic control on discriminative sensation of the hand, although a recent study revealed that DM patients might have worse moving and static 2PD sensations compared with the control group [24]. In addition, similar pinch strengths between the two subgroups with different levels of glycaemic control were found in this study, which supports the findings of a recent work with regard to there being no direct correlation between grip muscle strength and the value of HbA 1c [39].…”
Section: Discussionmentioning
confidence: 88%
“…For example, the patients with DM showed reduced force structural complexity (lower approximate entropy values) than healthy subjects when producing grip force upon a spatially fixed apparatus within 15–50% maximum voluntary contraction (MVC) 11 . Compared to the healthy subjects, the DM patients showed higher force ratio in execution of grip-to-lift task; and the force ratio could serve as indicator to DPN whose sensitivity was 85% and specificity was 51% 10 . The debilitated grip force in DM is associated with reduced tactile sensitivity, blurred afferent inputs and reduced efferent conductivity 10 13 , and is related to the impaired neuromuscular control for hand and digits due to the long-term hyperglycemia 4 , 14 17 .…”
Section: Introductionmentioning
confidence: 85%
“…Quantitative evaluation of the hand sensorimotor function provides a useful tool for clinical diagnosis of DPN 10 . Accumulating evidence suggests that the effects of DM on hand sensorimotor function could be observed from precision grip – a fundamental grasping manner with opposable thumb and index finger.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of median neuropathy among diabetes patients has been reported to be approximately 58-82%, based on an electrophysiological study 11 . Electrophysiological measurements can be used to show abnormalities of nerve functioning in the hand, especially with regard to the sensory amplitude of nerve conduction [12][13][14] . The consequences of abnormal sensory functioning of the nerve system as a result of the involvement of an impaired median nerve, ulnar nerve or both, might gradually contribute to different severities of neuropathic signs and symptoms, finally developing as mononeuropathy or polyneuropathy 15,16 .…”
Section: Introductionmentioning
confidence: 99%